The Influence of Democratic Leadership and Motivation to the Employee Performance of Medicine and Health Fields - Mawadi, Yusuf; ., Mattalatta; Mattalatta, Solihin; Limantara, Lily Montarcih (Journal of Ecohumanism, 2025)
This research intends to investigate the influence of democratic leadership and motivation to the employee performance of medicine and health fields through work discipline in Regional Police Office of South Sulawesi. The high-risk tasks are very basic reasons of the need for increasing the effort of Polri (Indonesian Republic Police) member welfare and families including the improvement of health quality and guarantee, because it will have implications to the performance increasing of the Polri member. The methodology consists of analysing the influence of democratic leadership (X1), and motivation (X2) to the work discipline; the influence of democratic leadership (X1), and motivation (X2) to the employee performance (Z); and the influence of work discipline (Y) to the employee performance (Z). The result shows that variables of democratic leadership and motivation have positive and significant influence to the work discipline at medicine and health fields in Regional Police Office of South Sulawesi, variables of democratic leadership and motivation have positive and significant influence to the employee performance at medicine and health fields in Regional Police Office of South Sulawesi, and variable of work discipline has positive and significant influence to the employee performance at medicine and health fields in Regional Police Office of South Sulawesi.